Threats and ensuring information security in crisis management systems - Jurek Michał; Staruch Marcin (2019)
Constantly progressing technical and technological development has allowed the creation of IT tools, the use of which will positively affect the actions taken by decision-makers. However, in order to be able to use them properly, in addition to thoroughly familiarizing themselves with their capabilities, it is necessary to develop operating schemes, e.g. human management, taking into account the use of the tools discussed in the article. When creating appropriate solutions, special attention should be paid to the possibility of securing information and data on which we will operate. This will be especially important during a crisis situation such as a flood, for example, where properly coordinated actions will allow a more effective rescue action. This will translate into lowering material and human losses. It should be remembered, however, that IT tools should always play a supporting role, and all decisions should be made after their prior assessment by a suitably qualified person.